Introduction of a partial shift system for house officers in a teaching hospital. Issue 6860 (24th October 1992) - Vassallo, D. J.; Chana, J.; Clark, C. L.; Smith, R. E.; Wood, R. F.
Abstract : OBJECTIVES–(1) To introduce a partial shift system to reduce the hours of work of preregistration house surgeons to an average of 64 a week to comply with the New Deal for junior doctors; (2) to test linking the partial shift concept to an existing structure of "on call" firms. DESIGN–Formal assessment after three months of a pilot partial shift system for eight house surgeons on three firms instituted on 1 November 1991, followed by questionnaire and interview evaluation at three and six months of a revised system implemented on 1 February 1992. SETTING–Department of general surgery at St Bartholomew's Hospital, London. SUBJECTS–24 house surgeons attached to three surgical firms. RESULTS–In eight weeks each house surgeon worked one week (five shifts) of night duty, one week of "cover" (afternoon and evening) duty, and six weeks of normal daytime hours. Each weekday a house surgeon from the firm on call worked an extended daytime on call shift until 10 pm. Weekend duties were split between two house surgeons from the firm on call. A computer generated graphical display of the rota was used to facilitate leave planning. Average working hours were reduced to below 64 per week, including prospective cover, without detriment to patient care and educational standards. Within the shift system individual house surgeons could be on call with their own firm by day and at weekends. Opinions were equally divided among junior staff as to their preference for either on call or partial shift systems. CONCLUSIONS–The principles of this partial shift system are generally applicable and the model can readily be adopted by district general hospitals.